Characterization of the electrical behavior of a discontinuous hybrid yarn textile made of recycled carbon and PA6 fibers during Joule heating. (October 2020) - Reese, Julian; Hoffmann, Gerald; Fieres, Johannes; Cherif, Chokri
The Joule heating of carbon fiber-based textiles enables an energy- and cost-efficient processing of carbon fiber reinforced thermoplastic parts. This article introduces a new method to pass direct current into a dry, not pre-consolidated hybrid yarn textile based on recycled carbon fibers and polyamide 6 fibers. The aim is to melt polyamide fibers, subsequently impregnate carbon fibers, and finally consolidate the material to form a composite part in a single process step. To increase the reliability of this technology, the electrical properties and the behavior of the material during the heating process must be thoroughly investigated. It will be addressed how the material is characterized during the process and how the changing resistivity of the textile affects the current flow between the electrodes to generate intrinsic heat. Moreover, a method to determine the effective material resistivity by finite element simulation on the fiber scale based on a CT scan is presented. Thus, a validated material model with respect to the temperature development in the textile based on ρ = ρ (Τ) was established.